3
$\begingroup$

How would I solve the following

$$\int x^3 e^{-x^2}\,dx$$

I set $u=e^{-x^2}(-2x)$ $du=e^{-x^2}(2x)$ $dv=x^3$ $v=\frac{x^4}{4}$

Then I did

$$e^{-x^2}\frac{x^4}{4}+\frac{1}{2}\int x^4e^{-x^2}(-x) \, dx$$

But I find myself stuck unfortunatly.

$\endgroup$
6
$\begingroup$

Hint: Make the preliminary substitution $t=x^2$. You will end up with something familiar.

But if you wish you can let $u=x^2$ and $dv=xe^{-x^2}\,dx$. The integration by parts will proceed smoothly.

$\endgroup$
5
  • $\begingroup$ Yes I think I will take one try let me see. $\endgroup$ – Fernando Martinez Sep 6 '13 at 19:47
  • $\begingroup$ I think the final answer shall be $x^2-\frac{1}{2}e^{-x}+1(-1/2)e^{-x^2}+C$ $\endgroup$ – Fernando Martinez Sep 6 '13 at 19:49
  • 1
    $\begingroup$ I get $-\frac{1}{2}x^2e^{-x^2}-\frac{1}{2}e^{-x^2}+C$ $\endgroup$ – André Nicolas Sep 6 '13 at 19:56
  • $\begingroup$ +1. Maybe I could impose on you for advice as to how one could naturally come up with the $t = x^2$ substitution. Thanks. Regards, $\endgroup$ – user12802 Sep 11 '13 at 23:22
  • $\begingroup$ Well, if one is looking for a "$u$-substitution," the general rule is that you let $u$ be whatever is Ugly. Anyway, $u=x^2$ is tempting. It would be nice if its derivative $2x$ were sitting in front. It sort of is, disguised as $x$, with another $x^2$ thrown in, but that's just $u$, so apart from a constant we will be looking at $ue^u$, doable, or at least simpler. We do all this while scanning the function, without writing anything. And then when it looks as if it will work, we start doing the details. $\endgroup$ – André Nicolas Sep 11 '13 at 23:30
3
$\begingroup$

\begin{align} \int x^{3}{\rm e}^{-x^{2}}\,{\rm d}x &= \left.-\,{\partial \over \partial\mu} \int x{\rm e}^{-\mu x^{2}}\,{\rm d}x\right\vert_{\mu = 1} = \left.-\,{\partial \over \partial\mu} \left(-\,{{\rm e}^{-\mu x^{2}} \over 2\mu}\right)\right\vert_{\mu = 1} \\[3mm]&= \left.\left(% -\,{x^{2}{\rm e}^{-\mu x^{2}} \over 2\mu} - {{\rm e}^{-\mu x^{2}} \over 2\mu^{2}} \right)\right\vert_{\mu = 1} = -\,{x^{2}{\rm e}^{-x^{2}} \over 2} - {{\rm e}^{-x^{2}} \over 2} = \color{#ff0000}{\large% -\,{1 \over 2}\left(x^{2} + 1\right){\rm e}^{-x^{2}}} \end{align}

$\endgroup$
1
$\begingroup$

Hint: $$\int x^3 e^{-x^2}dx=\frac12 \int x^2e^{-x^2}d(x^2)=\frac12 \int ye^{-y}dy.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.